Relevansi Ajaran Fiqh Dalam Kitab Bidayatul Hidayah Bagi Pengembangan Kurikulum Pendidikan Agama Islam - Faruqi Ali, Muhamad Mauris; Wawan Hermawan; Cucu Surahman (IAIN Ambon, 2024)
The Bidayatul Hidayah book by Imam Al-Ghazali is a classic text that discusses the teachings of fiqh and ethics comprehensively. This book is very relevant in the context of moral, spiritual development and character formation of Muslims. In developing the Islamic Religious Education (PAI) curriculum, Bidayatul Hidayah offers an important pedagogical foundation for building strong religious values ​​in students. This research aims to examine the relevance of the fiqh teachings contained in the book in order to support the development of the PAI curriculum in schools. By using the literature review method, this research was able to find that the principles of fiqh conveyed in Bidayatul Hidayah can be integrated into various aspects of PAI learning, especially in terms of building Islamic character, strengthening discipline in carrying out a worship service, as well as increasing understanding of Islamic law. Islamic law. It is hoped that the results of this study will be able to provide a significant contribution in designing a PAI curriculum that is more contextual, applicable and in line with the needs of current developments. Keywords: Bidayatul Hidayah, Curriculum,Islamic education, Curriculum Development